Smart Education and e-Learning 2019 - Uskov, Vladimir L.; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book contains the contributions presented at the 6th international KES conference on Smart Education and e-Learning (KES SEEL-2019), which took place at St. Julian's, Malta, June 17-19, 2019. It contains fifty-five high-quality peer-reviewed papers that are grouped into several interconnected parts: Part 1 - Smart Education, Part 2 - Smart e-Learning, Part 3 - Smart Pedagogy, Part 4 - Smart Education: Systems and Technology, Part 5 - Smart Education: Case Studies and Research, Part 6 - Students with Disabilities and Smart Education/University, and Part 7 - Mathematical Modelling of Smart Education and Economics of Smart University. Smart education and smart e-learning are emerging and rapidly growing areas with the potential to transform existing teaching strategies, learning environments, and educational activities and technology in the classroom. Smart education and smart e-learning focus on enabling instructors to develop new ways of achieving excellence in teaching in highly technological smart classrooms, and providing students with new opportunities to maximize their success and select the best options for their education, location and learning style, as well as the mode of content delivery. This book serves as a useful source of research data and valuable information on current research projects, best practices and case studies for faculty, scholars, Ph.D. students, administrators, and practitioners - all those who are interested in smart education and smart e-learning.
Part 1: Smart Education -- Chapter 1. Smart University: A Validation of "Smartness Features - Main Components" Matrix by Real World Examples and Best Practices from Universities Worldwide -- Chapter 2. Quantitative Follow-up of MOOC Students Using Big Data Techniques -- Chapter 3. Classification of University Students Attending Computing Classes Using a Self-Assessment Questionnaire -- Chapter 4. Smart Education in an Interconnected World: Virtual, Collaborative, Project-Based Courses to Teach Global Software Engineering -- Chapter 5. Smarter Education: Leveraging Stakeholder Inputs to Develop Work Ready Curricula -- Part 2: Smart e-Learning -- Chapter 6. Teaching Culture and Literature of German-Speaking Countries with the Support of Virtual Learning Environment in Reflection and Self-Reflection of Students of Management of Tourism - A Case Study -- Chapter 7. Sampling and Analyzing Statistical Data to Predict the Performance of MOOC -- Chapter 8. The Development of Classroom Research Skills of Online Lessons Usage of a Google Classroom -- Chapter 9. Interculturality in Blended Learning: Challenges of Electronic Communication -- Chapter 10. Machine Learning Approach of Predicting Learning Outcomes of MOOCs to Increase Its Performance -- Chapter 11. A Development of Instructional Games for Education Students -- Chapter 12. The Methodology of Development of Electronic Educational Resources for Learning of General Scientific Disciplines in Non-Native Language -- Chapter 13. Visualization of Learning Activities in Classroom Blended with e-Learning System -- Chapter 14. Dosage Effects of CAI on Literacy Skills -- Chapter 15. Construction of a Socio-Affective Profile Model of Students in a Virtual Learning Environment. .
Keywords: Computational intelligence; Artificial intelligence; Education -- Economic aspects; Computational Intelligence; Artificial Intelligence; Education Economics